PENEGAKAN HUKUM TERHADAP PELAKU EKSPLOITASI ANAK MELALUI MEDIA SOSIAL - Harahap, Siti Hajar (Universitas Muhammadiyah Ponorogo, 2024)
Today's advances can be gained very easily, namely through social media. Many people abuse technology to gain profit, one of which is exploiting children through social media. The criminal act of child exploitation is control, extortion, exploitation, use (of a person's energy or physical body) of oneself or another person for personal gain and is a disgraceful act. The problem and aim of this research is to find out the form of criminal acts of child exploitation based on the law; know about legal protection for children as victims of criminal acts of child exploitation through social media at the Medan Police PPA Unit, and know about law enforcement against perpetrators of child exploitation through social media at the Medan Police PPA Unit. The research method carried out is an empirical juridical research method (field research) supported by library research. This research resulted in the conclusion that criminal acts of exploitation according to law are divided into three, namely economic exploitation, sexual exploitation and social exploitation. Victims of child exploitation have the right to reparations, protection from further violence, and access to legal representation. Law enforcement officers not only have the responsibility to protect children from exploitation, but also those closest to the victims.